Outcome and prognostic factors in childhood B non-Hodgkin lymphoma from India: Report by the Indian Pediatric Oncology Group (InPOG-NHL-16-01 study). (15th August 2022) - Rahiman, Emine A.; Bakhshi, Sameer; , Deepam Pushpam; Ramamoorthy, Jaikumar; Das, Anirban; Ghara, Niharendu; Kalra, Manas; Kapoor, Gauri; Meena, Jagdish Prasad; Siddaigarhi, Sirisharani; Thulkar, Sanjay; Sharma, Meher Chand; et al.
Abstract: The literature on B-non-Hodgkin lymphoma (NHL) in India is restricted to individual hospital data. The study aimed to evaluate the epidemiology and outcome of B-NHL in our country. One hundred and ninety-one patients of B-NHL from 10 centers diagnosed between 2013 and 2016 were analyzed retrospectively. B/T lymphoblastic lymphoma and patients with inadequate data were excluded. The median age was 88 months (IQR: 56, 144) with an M:F ratio of 5.6:1. Undernourishment and stunting were seen in 36.5% and 22%. Primary site was abdomen in 66.5%. Hypoalbuminemia was noted in 82/170 (48.2%). Histological subtypes: Burkitt lymphoma (BL): 69.6%, Burkitt-like: 10.4%, and diffuse large B cell lymphoma (DLBCL): 13.6%, unclassified and others (6.4%). Stage distribution: I/II, 33 (17.3%), III, 114 (59.7%), and IV, 44 (23%). One-eighty-six patients took treatment. Protocols used were LMB and BFM in 160/186 (86%). At a median follow-up of 21.34 (IQR: 4.34, 36.57) months, the disease-free-survival (DFS) was 74.4% and event-free-survival (EFS) was 60.7%. Treatment-related mortality (TRM), relapse/progression and abandonment were 14.3%, 14.5%, and 8.4%, respectively. Bone marrow positivity, stage IV disease, and lactate dehydrogenase (LDH) > 2, 000 U/l predicted inferior EFS. Stage IV disease, LDH > 2, 000 U/l, bone marrow positivity, tumor lysis syndrome and low albumin predicted TRM; LDH retained significance on multivariate analysis for EFS and TRM [OR: 4.54, 95% CI: 1.14–20, p 0.03; OR 20, 95%CI: 1.69–250, p 0.017]. BL was the main histological subtype. High TRM and relapse/progression are hampering survival. An LDH > 2, 000 U/l was adversely prognostic. These data demonstrate a need to develop a national protocol that balances toxicity and potential for cure.